A conceptual model of enhancing spatial ability through immersive learning environment for art students - Yi, Jian (2024)
Spatial ability is an essential cognitive ability in spatial cognition, which plays a vital role in daily life or diverse subject areas. Especially in art education, spatial ability has become critical because of its unique functions in developing creativity. However, in the current art education, the importance of spatial ability has not received enough attention. Traditional classroom teaching lacks the conditions (such as technical tools) to develop spatial ability. Conversely, most art courses are carried out by two-dimensional media presentation, which is not conducive to developing students' spatial ability and understanding of spatial concepts. Therefore, adopting more suitable teaching tools and innovative teaching environments has become necessary to develop spatial ability. Thus, this study mainly explores how an immersive learning environment (ILE) built based on virtual reality (VR) technology will affect students' spatial ability, especially learning performance. The objectives of this study are (i) to determine the factors that enhance spatial ability through the immersive learning environment in art education, (ii) to construct a conceptual model of enhancing spatial ability through the immersive learning environment in art education based on the identified factors, (iii) to evaluate a conceptual model of enhancing spatial ability through the immersive learning environment in art education by the changes in students' learning performance. This study selected 58 first-year college art students as participants in the experiment. The change in students' learning performance before and after the experiment was compared to evaluate the effectiveness of the ILE conceptual model in enhancing students' spatial ability. The results show, among other findings, that ILE mode can better help students' learning, improve their spatial ability and academic skills, and stimulate their spatial imagination and spatial thinking abilities with a significant difference of 4.621 mean values compared with traditional mode. From the perspective of the educational needs of art students to cultivate spatial ability, this study provides a conceptual model of enhancing spatial ability through the immersive learning environment for art students with the empirical demonstration of the use of VR technology.